Seroprevalence of SARS-CoV-2 antibodies in dogs and cats during the early and mid-pandemic periods in Japan - Yamayoshi, Seiya; Ito, Mutsumi; Iwatsuki-Horimoto, Kiyoko; Yasuhara, Atsuhiro; Okuda, Moe; Hamabata, Taiki; Murakami, Jurika; Duong, Calvin; Yamamoto, Tsukasa; Kuroda, Yudai; Maeda, Ken; Kawaoka, Yoshihiro (One Health, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has continued to circulate in humans since its emergence in 2019. While infection in humans continues, numerous spillover events to at least 32 animal species, including companion and zoo animals, have been reported. Since dogs and cats are highly susceptible to SARS-CoV-2 and have direct contact with their owners and other household members, it is important to know the prevalence of SARS-CoV-2 in dogs and cats. Here, we established an ELISA to detect serum antibodies against the receptor-binding domain and the ectodomain of the SARS-CoV-2 spike and nucleocapsid proteins. Using this ELISA, we assessed seroprevalence in 488 dog serum samples and 355 cat serum samples that were collected during the early pandemic period (between May and June of 2020) and 312 dog serum samples and 251 cat serum samples that were collected during the mid-pandemic period (between October 2021 and January 2022). We found that two dog serum samples (0.41%) collected in 2020, one cat serum sample (0.28%) collected in 2020, and four cat serum samples (1.6%) collected in 2021 were positive for antibodies against SARS-CoV-2. No dog serum samples collected in 2021 were positive for these antibodies. We conclude that the seroprevalence of SARS-CoV-2 antibodies in dogs and cats in Japan is low, suggesting that these animals are not a major SARS-CoV-2 reservoir.